New records of Hedychium hookeri (Zingiberaceae) from China and Myanmar - Bai, Lin; Hu, Xiu; He, Jianghai; Tian, Zhongcheng (Phytotaxa, 2021)
Hedychium hookeri is newly recorded from China and Myanmar. A full description of the species, a colour plate showing diagnostic features of the species as well as some relevant taxonomic and nomenclatural notes and a detailed comparison of H. hookeri and its close relatives are provided. A lectoptype is designated for H. hookeri.